The performance of initial public offering (IPO) in Malaysia - Julia, binti Joni (Universiti Malaysia Sarawak (UNIMAS), 2010)
(fhe objective of this research paper is to evaluate the performance of Initial Public offering in Malaysia during year 2006 until 2009. It is investigate the determinants of the short and long run ofIPOs performance. This study produces information about the degree of underpricing and long run return of IPOs up to I-year, 2-years and 3 -years and their determinants which are variable to investors in designing their security selection processes The evidence indicates that, on average, the IPOs are underpriced. On the other hands, the IPOs show a pattern of underperformance (negative return) in the long run up to three years. However, the statistical evidence showed that in the long run the IPOs are neither under nor overpriced. Through statistical analysis of the dependency of several independent variables, it is found that only Offer to Open, Offer Size, Age of the firm and Lead Underwriter are significant influence the initial return for one year buy and hold abnormal return model.